2020
DOI: 10.48550/arxiv.2005.10743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tensor Clustering with Planted Structures: Statistical Optimality and Computational Limits

Abstract: This paper studies the statistical and computational limits of high-order clustering with planted structures. We focus on two clustering models, constant high-order clustering (CHC) and rank-one higher-order clustering (ROHC), and study the methods and theories for testing whether a cluster exists (detection) and identifying the support of cluster (recovery).Specifically, we identify sharp boundaries of signal-to-noise ratio for which CHC and ROHC detection/recovery are statistically possible. We also develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 67 publications
(130 reference statements)
1
14
0
Order By: Relevance
“…Indeed, the minimal requirements on SNR (often refereed to as the computational limits) for guaranteeing the existence of a polynomial-time initialization algorithm are generally unknown for most low-rank tensor models, even for the simple tensor PCA model. Interested readers are suggested to refer (Zhang and Xia, 2018;Luo and Zhang, 2020;Hopkins et al, 2015;Dudeja and Hsu, 2020;Arous et al, 2018) for the discussions on the computational hardness of tensor PCA. The computational limits are probably more difficult to study under generalized low-rank tensor models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the minimal requirements on SNR (often refereed to as the computational limits) for guaranteeing the existence of a polynomial-time initialization algorithm are generally unknown for most low-rank tensor models, even for the simple tensor PCA model. Interested readers are suggested to refer (Zhang and Xia, 2018;Luo and Zhang, 2020;Hopkins et al, 2015;Dudeja and Hsu, 2020;Arous et al, 2018) for the discussions on the computational hardness of tensor PCA. The computational limits are probably more difficult to study under generalized low-rank tensor models.…”
Section: Discussionmentioning
confidence: 99%
“…An mth-order tensor is a multilinear array with m ways, e.g., matrices are second order tensors. These multi-way structures often emerge when, to name a few, information features are collected from distinct domains Han et al, 2020;Bi et al, 2018;Zhang et al, 2020b;Wang and Zeng, 2019), the multi-relational interactions or higher-order interactions of entities are present (Ke et al, 2019;Jing et al, 2020;Kim et al, 2017;Paul and Chen, 2020;Luo and Zhang, 2020;Wang and Li, 2020;Ghoshdastidar and Dukkipati, 2017;Pensky and Zhang, 2019), or the higher-order moments of data are explored Sun et al, 2017;Hao et al, 2020). There is an increasing demand for effective methods to analyze large and complex tensorial datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…r pd{2 q) in tensor regression and least singular value requirement (λ{σ ě Opp d{4 r1{4 q) in tensor SVD match the start-of-the-arts in literature (see Table 1 for a comparison). Rigorous evidence has been established to show that the least singular value lower bounds in tensor SVD are essential for any polynomial-time algorithm to succeed (Zhang and Xia, 2018;Brennan and Bresler, 2020;Luo and Zhang, 2020b). Although no rigorous evidence has been established at present, it has been conjectured that the sample complexity Op ?…”
Section: Tensor Svdmentioning
confidence: 99%
“…As sketched in [43, Appendix A], this class contains many popular and powerful frameworks, including local algorithms on graphs, power iteration, and approximate message passing [35,11,56,64,36]. In addition, a recent flurry of work has shown that for many average-case problems in high-dimensional statistics, including planted clique, sparse PCA, community detection, and tensor PCA, low degree polynomials are as powerful as the best polynomial-time algorithms known [55,54,53,7,61,34,22,15,63,70,8,16]. Thus, showing that low degree polynomial algorithms fail at some threshold provides evidence that all polynomial-time algorithms fail at that threshold.…”
Section: Introductionmentioning
confidence: 99%